DOI: 10.25148/etd.fi10022523
|View full text |Cite
|
Sign up to set email alerts
|

Investigative Interviewing and Memory: How Accurate Are Interviewers’ Recollections of Investigative Interviews?

Abstract: DEDICATIONThis dissertation is dedicated to the loving memory of my grandfather, Bernard Hyman.Though he did not live to see me accomplish this goal, I never would have made it this far without his spirit heartening me to want and seek more out of life.iv ACKNOWLEDGMENTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…We demonstrated the predicted superiority of note taking as an external memory aid. This finding corresponds to prior studies that compared the quality of written records performed based on internal and external memory aids (Hope et al, ; Hyman Gregory, ; Hyman Gregory, Schreiber Compo, Vertefeuille, & Zambruski, ; Rosenhan et al, ). The amount of correctly recalled information was about 65% when participants took notes during the video.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We demonstrated the predicted superiority of note taking as an external memory aid. This finding corresponds to prior studies that compared the quality of written records performed based on internal and external memory aids (Hope et al, ; Hyman Gregory, ; Hyman Gregory, Schreiber Compo, Vertefeuille, & Zambruski, ; Rosenhan et al, ). The amount of correctly recalled information was about 65% when participants took notes during the video.…”
Section: Discussionsupporting
confidence: 89%
“…We also predicted that the usage of technical devices or note taking during the witness statement should improve the accuracy of the officer reports compared with reports that are based on a free recall of witness statements (cf. Hyman Gregory, ; Thorley, Baxter, & Lorek, ). Moreover, the quality of written records should be higher when (self‐administered) strategies of the cognitive interview are applied while performing the written record of an eyewitness testimony compared with records that are produced based on a free recall of witness statements.…”
Section: Introductionmentioning
confidence: 99%
“…Though this is changing, currently, not all witness interviews are recorded; therefore, investigators' accurate representation of what a witness said is critical. Hyman Gregory [79] found that those who took notes during investigative interviews included more information and had a greater percentage of accurate information in their post-interview report (written two weeks after the interview). While taking notes is better than not, other research reminds us that notes are necessarily incomplete; in one study, 25% of incident-relevant details were not recorded in interviewers' notes [80].…”
Section: Courtroommentioning
confidence: 98%
“…Hence, asking open questions is an important feature of an investigative interview (Danby et al, 2017). Interviewers must then accurately remember the often-numerous details provided by interviewees but interviewers' recall of information may be limited and inaccurate (Hyman- Gregory, 2009).The interviewer may introduce this erroneous information to the witness, which may have an impact on the subsequent accuracy and reliability of the witness's testimony (Gudjonsson, 2010;Loftus & Pickrell, 1995). In doing this, interviewers can affect the amount and quality of evidence provided by witnesses (Brown & Lamb, 2015;Gudjonsson, 2010).…”
Section: Cognitive Load In Investigative Interviewsmentioning
confidence: 99%